1964
DOI: 10.1063/1.1726291
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Infrared Intensities of the Fundamental Absorption Bands in Solid CO2 and N2O

Abstract: Absolute infrared intensities of the fundamental vibrations of CO2 and N2O have been measured in polycrystalline solid films. The path length has been measured by observing interference fringes. In contrast with CS2, the results for the solid phase do not agree exactly with those predicted from the gas phase values, using only the simple ``field-effect'' correction. In particular the intensity in the solid is less than that in the gas phase for v1 and v3 of N2O and for v3 of CO2, whereas the ``field-effect'' p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
56
0

Year Published

1967
1967
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(64 citation statements)
references
References 20 publications
8
56
0
Order By: Relevance
“…However, the ratio calculated using the second method depends on the band strengths provided by the literature. The band strength for the CO 2 asymmetric stretching band at 2340 cm −1 was measured to be 7.6 × 10 −17 cm molecule −1 for the pure solid (Yamada & Person 1964;Gerakines et al 1995), while in water ice a value of 1.4 × 10 −16 cm molecule −1 was found (Sandford & Allamandola 1990). The band strength for the wagging mode of NH 3 at 1070 cm −1 varies from 1.3 × 10 −17 to 1.7 ×10 −17 cm molecule −1 (Kerkhof et al 1999;d'Hendecourt et al 1986) in its pure solid form.…”
Section: Description Of Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the ratio calculated using the second method depends on the band strengths provided by the literature. The band strength for the CO 2 asymmetric stretching band at 2340 cm −1 was measured to be 7.6 × 10 −17 cm molecule −1 for the pure solid (Yamada & Person 1964;Gerakines et al 1995), while in water ice a value of 1.4 × 10 −16 cm molecule −1 was found (Sandford & Allamandola 1990). The band strength for the wagging mode of NH 3 at 1070 cm −1 varies from 1.3 × 10 −17 to 1.7 ×10 −17 cm molecule −1 (Kerkhof et al 1999;d'Hendecourt et al 1986) in its pure solid form.…”
Section: Description Of Experimental Methodsmentioning
confidence: 99%
“…The values of the band strengths for these two molecules depend on the nature, composition, and temperature of the ice in which they are found. We therefore used the values given by Yamada & Person (1964) for CO 2 (7.6×10…”
Section: Description Of Experimental Methodsmentioning
confidence: 99%
“…The ISAC set-up is an ultra-high vacuum (UHV) chamber with a pressure about 4 × 10 −11 mbar, which corresponds to a density of 10 6 cm −3 (Muñoz Caro et al 2010), similar to that found in dense cloud From Jiang et al (1975). (c) From Yamada & Person (1964). (d) From d 'Hendecourt & Allamandola (1986).…”
Section: Methodsmentioning
confidence: 99%
“…Next, after fitting a straight baseline, we calculated the band area, divided by the band strength A, and corrected for 45 • incidence, to obtain the column density of the film. To quantify the optical depth we assumed that the band strengths of 13 CO and 13 CO 2 were the same as for 12 CO and 12 CO 2 , A = 7.6 × 10 −17 cm molecule −1 ( 13 CO 2 ) and A = 1.1 × 10 −17 cm molecule −1 ( 13 CO) (Yamada & Person 1964;Jiang et al 1975). Comparing the column density measured by infrared spectroscopy with the film thickness measured by laser interferometry (Baratta & Palumbo 1998), we derive that the density of the CO film in our experimental conditions is 0.81 g cm −3 .…”
Section: Experimental Methodsmentioning
confidence: 99%